Do Commercial Banks’ Non-Performing Loans Respond to Environmental Financial and Economic Influences in the Sub-Saharan Region of Africa? - Asemota, Georgina; Erhi, Moses Akpesiri; Ihensekhien, Orobosa (Acta Universitatis Danubius. Œconomica, 2023)
This study investigates the influence of financial and macroeconomic variables on non-performing loans using 27 countries from sub-Saharan Africa. The study sourced data for the period 2012 to 2021. To ascertain financial influences, bank-related variables representing bank operations and bank quality were chosen. For the macroeconomic influences, monetary policy variables and variables representing the macroeconomic conditions were chosen. Based on the preliminary data investigation results and subsequent findings in the course of the study, three estimators- Dynamic Generalized Method of Moments (GMM), System GMM (SYS-GMM) and system Seemingly Unsure Regression (SYS-SUR) - were used to analyze the data. The results confirm that bank quality; monetary policy and bank operations were significant determinants of the variations in non-performing loans in the region. The paper concludes that nonperforming loans do respond to environmental both financial and economic environmental influences. It then recommends that monetary authority should use monetary tools such as interest rates or required reserve ratio instead of the money supply since those tools do not have any impact on NPLs. Strict monitoring of commercial banks is also recommended.